Haloquadratum walsbyi yields a versatile, NAD+/NADP+ dual affinity, thermostable, alcohol dehydrogenase (HwADH) - Cassidy, Jennifer; Paradisi, Francesca (Springer, 2018)
This study presents the first example of an alcohol dehydrogenase (ADH) from the halophilic archaeum Haloquadratum walsbyi (HwADH). A hexahistidine-tagged recombinant HwADH was heterologously overexpressed in Haloferax volcanii. HwADH was purified in one step and was found to be thermophilic with optimal activity at 65 °C. HwADH was active in the presence of 10 % (v/v) organic solvent. The enzyme displayed dual cofactor specificity and a broad substrate scope, maximum activity was detected with benzyl alcohol and 2-phenyl-1- propanol. HwADH accepted aromatic ketones, acetophenone and phenylacetone as substrates. The enzyme also accepted cyclohexanol and aromatic secondary alcohols, 1- phenylethanol and 4-phenyl-2-butanol. H. walsbyi may offer an excellent alternative to other archaeal sources to expand the toolbox of halophilic biocatalysts.